Judge knot : politics and development in international investment law / Todd N. Tucker. - Tucker, Todd N. (Anthem frontiers of global political economy., 2018)
'Judge Knot' explores the biggest and the most controversial success story in international law: investor-state dispute settlement, or ISDS. Since 1990, investors have launched hundreds of claims against government regulation. This exclusive inside look explains what makes the system tick: its poorly understood centuries-old origins, why corporations demand investment law solutions to political problems, how arbitrators supply these solutions, and why the system lasts despite the many politicians and citizens unhappy with it. Building off of an unprecedented set of interviews with the arbitrators who actually decide the cases, 'Judge Knot' brings together the best of political science, law and development economics scholarship and offers a concrete alternative to ISDS that leverages what works about the system and discards what does not, so that international law can be more supportive of democracy and development goals.